Pengaruh Penerapan Rekam Medis Elektronik terhadap Efisiensi Waktu Tunggu dan Mutu Pelayanan Pasien di Instalasi Gawat Darurat - Herwanto, Rio (Lembaga Teewan Journal Solutions, 2026)
Electronic Medical Record (EMR) implementation is a strategic digital transformation in healthcare. Pusdikkes Puskesad Hospital East Jakarta has implemented EMR since 2023, achieving an 85% implementation rate. However, patient waiting time inefficiencies in the Emergency Department (ED) persist due to technical constraints. This study aims to analyze the effect of EMR implementation on patient waiting time efficiency and service quality in the ED. A quantitative observational study with a cross-sectional design was conducted, involving 238 respondents selected through purposive sampling. Data were collected using an EMR implementation questionnaire (30 items), a waiting time observation sheet, and a service quality questionnaire (25 items), and analyzed using Chi-Square test (*p* < 0.05). Results showed that most respondents rated EMR implementation as good (75.6%), most patients experienced fast waiting times (84.0%), and most rated service quality as good (58.8%). Chi-Square analysis revealed significant effects of EMR implementation on waiting time efficiency (*p* = 0.005) and service quality (*p* = 0.029). In the good EMR group, 87.8% had fast waiting times and 62.8% rated service quality as good, compared to 72.4% and 46.6% in the poor EMR group. Good EMR implementation significantly improves patient waiting time efficiency and service quality in the Emergency Department.